Boron-incorporating hemagglutinating virus of Japan envelope (HVJ-E) nanomaterial in boron neutron capture therapy. Issue 1 (31st December 2019) - Yoneoka, Shuichiro; Nakagawa, Yasuhiro; Uto, Koichiro; Sakura, Kazuma; Tsukahara, Takehiko; Ebara, Mitsuhiro
ABSTRACT: Combining immunotherapeutic and radiotherapeutic technique has recently attracted much attention for advancing cancer treatment. If boron-incorporated hemagglutinating virus of Japan-envelope (HVJ-E) having high membrane fusion ability can be used as a boron delivery agent in boron neutron capture therapy (BNCT), a radical synergistic improvement of boron accumulation efficiency into tumor cells and antitumor immunity may be induced. In this study, we aimed to develop novel boron-containing biocompatible polymers modified onto HVJ-E surfaces. The copolymer consisting of 2-methacryloyloxyethyl phosphorylcholine (MPC) and methacrylamide benzoxaborole (MAAmBO), poly[MPC- co -MAAmBO], was successfully synthesized by using a simple free radical polymerization. The molecular structures and molecular weight of the poly[MPC- co -MAAmBO] copolymer were characterized by nuclear magnetic resonance and matrix-assisted laser desorption ionization time-of-flight mass spectrometry, respectively. The poly[MPC- co -MAAmBO] was coated onto the HVJ-E surface via the chemical bonding between the MAAmBO moiety and the sugar moiety of HVJ-E. DLS, AFM, UV-Vis, and fluorescence measurements clarified that the size of the poly[MPC- co -MAAmBO]-coated HVJ-E, HVJ-E/p[MPC-MAAmBO], to be about 130 150 nm in diameter, and that the polymer having 9.82 × 10 6 7 boron atoms was steadily coated on a single HVJ-E particle. Moreover, cellular uptake of poly[MPC- co -MAAmBO] could be demonstrated without cytotoxicity, and the hemolysis could be successfully suppressed by 20%. These results indicate that the HVJ-E/p[MPC-MAAmBO] may be used as boron nanocarriers in a combination of immunotherapy with BNCT. Graphical Abstract: uf0001